DISCRETE MATHEMATICS AS FUNDAMENTAL DISCIPLINE IS IN SYSTEM OF MATHEMATICAL PREPARATION OF FUTURE SOFTWARE ENGINEER (Journal of Information Technologies in Education (ITE), 2010)
Fundamental mathematical background is an important part of training future engineers and programmers. The paper considers existing approaches to teaching the fundamentals of discrete mathematics specialist IT profile, a comparative analysis of modern textbooks on discrete mathematics for IT professionals was conducted.
Keywords: discrete mathematics; fundamental training; programmers; the mathematical education of engineers